2022
DOI: 10.3389/fphar.2022.1016552
|View full text |Cite
|
Sign up to set email alerts
|

SNS-032 attenuates liver fibrosis by anti-active hepatic stellate cells via inhibition of cyclin dependent kinase 9

Abstract: Liver fibrosis is a common pathological process of all chronic liver diseases. Hepatic stellate cells (HSCs) play a central role in the development of liver fibrosis. Cyclin-dependent kinase 9 (CDK9) is a cell cycle kinase that regulates mRNA transcription and elongation. A CDK9 inhibitor SNS-032 has been reported to have good effects in anti-tumor. However, the role of SNS-032 in the development of liver fibrosis is unclear. In this study, SNS-032 was found to alleviate hepatic fibrosis by inhibiting the acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Other studies showed that YAP-TEAD activation requires TGFβ1 signaling in cancer-associated fibroblasts and pancreatic stellate cell myofibroblasts [ 64 , 65 ]. Similarly, BCL-2 levels have been shown to not be affected or transiently affected by TGFβ1 signaling [ 66 , 67 , 68 , 69 ]. It is crucial that similar results regarding YAP1 and BCL2 reduction upon 5-FU-miR-15a treatment were obtained from murine and human PSCs ( Figure 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies showed that YAP-TEAD activation requires TGFβ1 signaling in cancer-associated fibroblasts and pancreatic stellate cell myofibroblasts [ 64 , 65 ]. Similarly, BCL-2 levels have been shown to not be affected or transiently affected by TGFβ1 signaling [ 66 , 67 , 68 , 69 ]. It is crucial that similar results regarding YAP1 and BCL2 reduction upon 5-FU-miR-15a treatment were obtained from murine and human PSCs ( Figure 11 ).…”
Section: Discussionmentioning
confidence: 99%